2019
DOI: 10.1111/csp2.98
|View full text |Cite
|
Sign up to set email alerts
|

Social influence and forest habitat conservation: Experimental evidence from Vermont's maple producers

Abstract: Working landscapes can provide biodiversity and ecosystem services. Many voluntary conservation programs ask those who manage working lands-farmers, ranchers, and forest landowners-to steward their resources in ways that maintain or increase these benefits. While research on landowners suggests the importance of social influence in management decisions, few studies have tested whether providing information about the behavior and opinions of others affects decisions related to private land and forest management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 83 publications
(124 reference statements)
0
13
2
Order By: Relevance
“…Our findings regarding the overall ineffectiveness of the norms-only message are contrary to findings from recent studies that show sharing information about the large number of others engaging (or starting to engage) in a behavior can enhance conservation action (Geiger & Swim, 2016;Kusmanoff et al, 2020;Sparkman & Walton, 2017). However, several randomized control trials applying normative messaging to biodiversity conservation show null or even negative impacts of social norm interventions (Byerly et al, 2019;Niemiec et al, 2020b). Byerly et al (2019), for example, found that providing information to maple producers about the participation of others in a bird habitat conservation program had a negative effect on the number of producers requesting information about the program compared to an informationonly control.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings regarding the overall ineffectiveness of the norms-only message are contrary to findings from recent studies that show sharing information about the large number of others engaging (or starting to engage) in a behavior can enhance conservation action (Geiger & Swim, 2016;Kusmanoff et al, 2020;Sparkman & Walton, 2017). However, several randomized control trials applying normative messaging to biodiversity conservation show null or even negative impacts of social norm interventions (Byerly et al, 2019;Niemiec et al, 2020b). Byerly et al (2019), for example, found that providing information to maple producers about the participation of others in a bird habitat conservation program had a negative effect on the number of producers requesting information about the program compared to an informationonly control.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings regarding the overall ineffectiveness of the norms‐only message are contrary to findings from recent studies that show sharing information about the large number of others engaging (or starting to engage) in a behavior can enhance conservation action (Geiger & Swim, 2016 ; Kusmanoff et al., 2020 ; Sparkman & Walton, 2017 ). However, several randomized control trials applying normative messaging to biodiversity conservation show null or even negative impacts of social norm interventions (Byerly et al., 2019 ; Niemiec et al., 2020b ). Byerly et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, as with all interdisciplinary collaborations, these collaborations will have their challenges 75 . However, recent examples show that effective collaborations can produce novel and mutually beneficial research that suggests practical routes to achieving behaviour change for biodiversity conservation 50,64,[76][77][78] .…”
Section: Increasing Scientific Engagementmentioning
confidence: 99%
“…Here, we define non-adopters as those individuals who have not adopted any of a set of conservation practices for which they are eligible (see below). Many messaging studies test interventions drawn from behavioral economics and nudge theory (Thaler & Sunstein, 2008;Byerly et al, 2018), such as positive versus negative framing (Jacobson et al, 2019), information about social norms (Byerly et al, 2019), and appeals to empathy (Czap NV, Banerjee & Burbach, 2019), among others. However, among those studies that measure behavioral outcomes, the dependent variable is often whether respondents request further information (e.g., Dean, Fielding & Wilson, 2019;Reddy et al, 2020), which is a sufficiently different behavior from attending an outreach event to warrant caution in extrapolating findings.…”
Section: Introductionmentioning
confidence: 99%